Cardiovascular mortality and cardiovascular event rates in patients with inflammatory rheumatic diseases in the CARdiovascular in rheuMAtology (CARMA) prospective study—results at 5 years of follow-up - Martín-Martínez, María A; Castañeda, Santos; Sánchez-Alonso, Fernando; García-Gómez, Carmen; González-Juanatey, Carlos; Sánchez-Costa, Jesús T; Belmonte-López, María A; Tornero-Molina, Jesús; Santos-Rey, José; Sánchez González, Carmen O; Quesada, Estefanía; Moreno-Gil, María P; et al. (Rheumatology (Oxford, England), 2021)
Abstract Objectives To determine cardiovascular (CV) mortality and incidence of the first CV event (CVE) in patients with chronic inflammatory rheumatic diseases (CIRD) after 5 years of follow-up. Methods This is an analysis of the CARdiovascular in rheMAatology (CARMA) study after 5 years of follow-up. It includes patients with RA (n = 775), AS (n = 738) and PsA (n = 721), and individuals without CIRD (n = 677) attending outpatient rheumatology clinics from 67 public hospitals in Spain. Descriptive analyses were performed for the CV mortality at 5 years. The Systematic COronary Risk Evaluation (SCORE) function at 5 years was calculated to determine the expected risk of CV mortality. Poisson models were used to estimate the incidence rates of the first CVE. Hazard ratios of the risk factors involved in the development of the first CVE were evaluated using the Weibull proportional hazard model. Results Overall, 2382 subjects completed the follow-up visit at 5 years. Fifteen patients died due to CVE. CV deaths observed in the CIRD cohort were lower than that predicted by SCORE risk charts. The highest incidence rate of CVE [7.39 cases per 1000 person-years (95% CI 4.63, 11.18)] was found in PsA patients. However, after adjusting for age, sex and CV risk factors, AS was the inflammatory disease more commonly associated with CVE at 5 years [hazard ratio 4.60 (P =0.02)], compared with those without CIRD. Conclusions Cardiovascular mortality in patients with CIRD at 5 years of follow-up is lower than estimated. Patients with AS have a higher risk of developing a first CVE after 5 years of follow-up.